1997
DOI: 10.1128/jcm.35.6.1390-1393.1997
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic characterization of multidrug-resistant Mycobacterium bovis strains from a hospital outbreak involving human immunodeficiency virus-positive patients

Abstract: Nineteen multidrug-resistant (MDR) Mycobacterium complex strains isolated in a nosocomial outbreak were characterized at the molecular level. The strains were microbiologically characterized as Mycobacterium bovis. The mpt40 sequence was not present in chromosomal DNA from these strains, supporting the fact that they were M. bovis. All of the isolates were resistant to isoniazid, rifampin, pyrazinamide, ethambutol, streptomycin, para-aminosalicylic acid, clarithromycin, cycloserine, ethionamide, ofloxacin, cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 15 publications
0
23
0
3
Order By: Relevance
“…222 MDR-TB organisms also have been documented to be the cause of a nosocomial outbreak in Argentina. 223 Similarly, clonally-related strains of M. bovis resistant to INH, RIF, PZA, ETH, STR, AMI, CAP, para-aminosalicylic acid, clarithromycin, ethionamide, and ofloxacin caused 16 cases of tuberculosis in a nosocomial outbreak involving HIV-positive patients in Spain, 207,224,225 and transmission of this organism to an immunocompetent patient also has been documented. 226 These MDR isolates arise because random mutations in genes that encode targets for the individual antimicrobial agents are selected by subtherapeutic drug levels that can occur due to processes such as treatment errors, poor adherence to treatment protocols, or other factors.…”
Section: Multidrug-resistant Tuberculosismentioning
confidence: 99%
“…222 MDR-TB organisms also have been documented to be the cause of a nosocomial outbreak in Argentina. 223 Similarly, clonally-related strains of M. bovis resistant to INH, RIF, PZA, ETH, STR, AMI, CAP, para-aminosalicylic acid, clarithromycin, ethionamide, and ofloxacin caused 16 cases of tuberculosis in a nosocomial outbreak involving HIV-positive patients in Spain, 207,224,225 and transmission of this organism to an immunocompetent patient also has been documented. 226 These MDR isolates arise because random mutations in genes that encode targets for the individual antimicrobial agents are selected by subtherapeutic drug levels that can occur due to processes such as treatment errors, poor adherence to treatment protocols, or other factors.…”
Section: Multidrug-resistant Tuberculosismentioning
confidence: 99%
“…Middlebrook and Cohn [230] showed that some INH‐resistant strains were less pathogenic in guinea pigs and this was attributed to the reduction of the catalase activity in these bacteria. Despite this apparently reduced virulence of some INH‐resistant M. tuberculosis strains, many outbreaks of (multidrug) resistant strains were recorded with DNA fingerprinting methods [32, 138, 207, 208, 231–233]. The susceptibility of HIV‐positive patients to tuberculosis infections and the accelerated breakdown to disease often result in more rapid transmission of the disease, as indicated in many outbreaks investigated with DNA fingerprinting [31, 33–37, 234, 235].…”
Section: Transmission Of Resistant M Tuberculosis Strainsmentioning
confidence: 99%
“…MDR-TB cases have been reported in many regions of the World [12]. Although MDR-TB is mainly developed from infection with mycobacterium tuberculosis, MDR-M.bovis outbreaks have been reported [13,14]. In Spain, M.bovis strains resistant to both rifampin and isoniazid were isolated from tuberculosis patients [8].…”
Section: Introductionmentioning
confidence: 99%